PEMBERDAYAAN PENGELOLA LEMBAGA EKONOMI KOMUNITAS ADAT MELALUI PENGUASAAN TEKNOLOGI INFORMASI DI DESA JUNGUT KABUPATEN KLUNGKUNG, BALI - IDA AYU WIDANI SUGIANINGRAT; PUTU KRISNA ADWITYA SANJAYA; PUTU NURATAMA (JURNAL SEWAKA BHAKTI, 2019)
Village Credit Institutions are quite capable of accelerating the economy of traditional village manners to advance and make a significant contribution to village development. But in the midst of the frenzy of the era of digitalitation revolution 4.0 characterized by automation demanding a movement for renewal in the LPD in order to be able to compete with similar institutions. The fundamental problems of LPD that are most prominent are the capacity of Human Resources in terms of management, use of information technology, especially in the preparation of financial statements. In the digitalization era, every business actor must prepare himself to enter the 4.0 industrial revolution. For this reason, business actors are expected to maximize the use of information technology, one of which is in the preparation of financial statements. However, currently there are not many microfinance institutions that use information technology to carry out the recording of their financial statements. LPD still records finance conventionally. Of course this if it is not immediately followed up will pose a risk of loss in the future. Solution to problem solving is done by conducting socialization, mentoring the preparation of financial statements. The implementation method is carried out in several stages, beginning to provide an understanding of the importance of the use of information technology, conducting training in information technology-based financial report training, lastly assisted to solve problems related to the preparation of financial statements. The hope after this activity ends is that LPD is able to carry out its business activities independently to prepare financial reports and carry out evaluations of business activities and in the long run the LPD will develop and be able to torch accelerate the economy of the local village.